Kajian Peranan Konsultan Manajemen Konstruksi pada Proyek Konstruksi di Makassar - Amin, Burhamsyah; Ashad, Hanafi; Maricar, Husni (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Implementation of work on construction projects generally involves the collaboration of several parties, namely the work owner, contractors and consultants. There are several consultants involved in construction projects, one of which is Construction Management Consultants (MK). The success of the role of an MK consultant can be measured through achievements in terms of cost, time and quality of work. Research to examine the role of MK consultants at the construction project implementation stage and examine the influence of the role of MK consultants on the timeliness of work on the Rehabilitation project for Buildings B, C, D, Makassar Unhas Hospital. Quantitative research method with multiple linear regression analysis techniques. The results of the research are that the role of construction management consultants at the implementation stage of construction projects is carried out well based on the highest positive response (Agree), namely the capability of MK consultants in taking corrective action on deviations between planning and implementation (X4) reaching a value of 68.35% and the role of project management consultants positive influence or significance even though the correlation value is low on the progress of project work, the highest correlation value is on the variable (X2) consistency of MK consultant personnel in implementing existing plans with a value of 0.348 and the lowest correlation value on variable (X5) capability of MK consultants in management project costs to the progress of project work with a value of 0.088.